2021
DOI: 10.34172/ehem.2021.22
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary triclosan and methyl-triclosan levels with predictive indicators of cardiovascular disease and obesity in children and adolescents in 2020 (case study: Kerman, Iran)

Abstract: Background: Exposure of children and adolescents to endocrine disrupting chemicals (EDCs) causes the development of non-communicable diseases. Triclosan (TCS) is a fat-soluble antimicrobial agent, and methyl-triclosan (MTCS) is the predominant metabolite of TCS. The increasing use of consumables TCS (toothpaste, mouthwash, personal care products) in human has raised concerns about human health. Methods: The urinary concentrations of TCS and MTCS were measured by GC/MS. Lipid profiles (TG, TC, LDL, and HDL), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Recently, exposure to TCS and TCC has been associated with increased risk of childhood obesity, by examining in first morning urine of children aged 7–11 years by liquid chromatography coupled to mass spectrometry [ 195 ]. In another study in children, a relationship between TCS and its metabolite MTCS with predictive indicators of cardiovascular diseases and obesity was found [ 196 ]. A recent study on a total of 674 infertile Chinese women at 18–45 years of age showed that TCS exposure at a relatively low level was associated with PCOS [ 197 ].…”
Section: Toxicity Studies On Tcsmentioning
confidence: 99%
“…Recently, exposure to TCS and TCC has been associated with increased risk of childhood obesity, by examining in first morning urine of children aged 7–11 years by liquid chromatography coupled to mass spectrometry [ 195 ]. In another study in children, a relationship between TCS and its metabolite MTCS with predictive indicators of cardiovascular diseases and obesity was found [ 196 ]. A recent study on a total of 674 infertile Chinese women at 18–45 years of age showed that TCS exposure at a relatively low level was associated with PCOS [ 197 ].…”
Section: Toxicity Studies On Tcsmentioning
confidence: 99%
“…People who are overweight and obese during childhood are more likely to develop obesity, cardiovascular diseases such as hypertension, hyperlipidemia, and atherosclerosis during adulthood [ 6 ]. However, the spread of cardiovascular disease does not begin in childhood and adolescence, but the risk factors for cardiovascular disease often start in childhood and adolescence [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid increase in obesity in the young population, early detection of risk factors and their prompt treatment are important to prevent or delay the onset of late-stage heart disease complications [ 9 ]. The causes of obesity have been widely studied but are not yet well understood [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pollutant concentrations in serum may be indicative of their circulation across organs in the human body. As a result, a high-throughput extraction approach based on a tiny volume of serum sample is required, as well as an instrumental analysis method capable of detecting minuscule levels of contaminants with high precision [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%